1989
DOI: 10.1128/mcb.9.7.2906
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of OBF1: a Saccharomyces cerevisiae protein that binds to autonomously replicating sequences.

Abstract: We previously identified a protein activity from Saccharomyces cerevisiae, OBF1, that bound specifically to a DNA element present in autonomously replicating sequences ARS120 and ARS121 (S. Eisenberg C. Civalier, and B. K. Tye, Proc. Natl. Acad. Sci. USA 85:743-746, 1988). OBF1 has now been purified to near homogeneity by conventional protein and DNA affinity chromatography. Electrophoresis of the purified protein in sodium dodecyl sulfate-polyacrylamide gels revealed the presence of two polypeptides. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…For instance, the K625I mutation in the context of aa 1-662 results in a major defect in Abf1p nuclear localization and the corresponding mutant protein is grossly overexpressed. 2 In addition, the observation that more Abf1p-(1-643) is associated with endogenous promoters than the wild-type protein (Fig. 3) is also consistent with Abf1p-mediated negative autoregulation.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…For instance, the K625I mutation in the context of aa 1-662 results in a major defect in Abf1p nuclear localization and the corresponding mutant protein is grossly overexpressed. 2 In addition, the observation that more Abf1p-(1-643) is associated with endogenous promoters than the wild-type protein (Fig. 3) is also consistent with Abf1p-mediated negative autoregulation.…”
Section: Discussionsupporting
confidence: 59%
“…Among all of the abf1 mutant alleles examined in the study, a point mutation in CS1-(1-662/ K625I) that resulted in impaired nuclear localization exhibited the most striking phenotypes at both temperatures (lanes 5 and 12). 2 For instance, the Abf1p-repressed genes in the Abf1p-(1-662/K625I) mutant background were expressed at levels even higher than those in abf1-1. On the other hand, Abf1p-activated gene expression was significantly compromised in the 1-662/K625I mutant strain with some of the genes in this group expressed below detectable levels (e.g.…”
Section: Effects Of Multiple Mutant Alleles Of Abf1 On Abf1p-mediatedmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence analysis indicated that, contrary to earlier belief, ABFI and OBF1 both bind to the same consensus sequence that has been defined as the consensus ABFI binding sequence (9). It should be pointed out that the purification of the OBF1 protein was carried out by affinity chromatography on immobilized DNA that essentially contained multiple copies of this consensus ABFI binding sequence (20).…”
Section: Resultsmentioning
confidence: 65%
“…However, the possibility of the existence of a family of such ABFs could not be eliminated at the present time. As far as the identity between ABFI and OBF1 is concerned, Francesconi and Eisenberg (20) indicated that the purified OBF1 protein also bound to ARSI and HMRE-ARS; thus, the possibility exists that the ABFI and OBF1 proteins are similar. This proposal is strongly supported by the results presented in this report.…”
Section: Resultsmentioning
confidence: 99%